Peer Group Pressure As A Determinant Of Adolescent Social Adjustment In Nigerian Schools - A. Oni, Adesoji (Penerbit Universiti Sains Malaysia, 2010)
This study investigated peer group pressure as a determinant of adolescents' social adjustment in Nigerian schools, with a focus on the Ikeja Local Government Area of Lagos State. Two null hypotheses were tested using a random sample of one hundred and twenty adolescents from four secondary schools in the Ikeja Local Government Area. The instrument was a self-designed questionnaire. The collected data were analysed using an independent t-test and a Pearson Product Moment Correlation Coefficient. The results of the analysis showed that peer group pressure among adolescents is related to their social adjustment and that the gender of the adolescents affects their social adjustment as well. Based on these findings, the following recommendations are made: parents should serve as role models for their children to emulate; parents should be watchful of the types of friends kept by their adolescent children; and parent-child relationship should be cordial enough to permit adolescents in discussing their problems with them. In addition, the management of adolescents (secondary school students) should be the joint responsibility of parents, guidance counsellors, school administrators and society at large.